PENGARUH SUPERVISI AKADEMIK DAN SERTIFIKASI GURU TERHADAP KINERJA GURU SMK NEGERI 1 BOYOLANGU TULUNGAGUNG - Budi, Hardini; Musyafik, Naim (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Teachers have an important task which is to realize the goal of national education, develop capabilities and shape the character and civilization of a dignified nation in the context of educating the life of the nation, supporting the development of students' potentials to become people of faith and piety for God Almighty, of good character, healthy, knowledgeable, capable, creative, independent, and become citizens who are supported and responsible. Teacher performance is influenced by external factors and internal factors. This study aims to: (1) analyze the effect of academic supervision and certification on teacher performance; (2) analyzing academic supervision of teacher performance; and (3) analyzing certification of teacher performance. This research was conducted on teachers at Boyolangu State Vocational School 1. The results showed that: (1) simultaneous academic supervision and certification proved the teacher's performance; (2) partially academic supervision has a negative and significant effect on teacher performance; (3) partial certification is positive and significant towards teacher performance; and (4) the proportion of the influence of academic supervision and certification variables can be seen from the coefficient of determination (R2) which is equal to 0.480. Regarding academic supervision and certification influencing the Teacher Performance variable by 48% while the remaining 52% was approved by other variables not included in this analysis model.